Analisis Kedisiplinan Kerja Terhadap Kinerja Karyawan PT. Multi Garmen Jaya ( Cardinal ) - Fina, Alfina Fitriani; Amilia Tresnawati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
This research aims to find out about work discipline on employee performance at PT. Multi Garment Jaya. The type of research used is descriptive qualitative research, and data collection in this research used interviews with 3 informants to obtain the data sought. The results of this research are about the relationship between work discipline and employee performance which can be detrimental to the employees themselves, other employees, and of course the company. The company's efforts to improve work discipline and improve performance by implementing types of violations such as warning letters with warnings can increase employee performance and can complete the tasks given by the company to the maximum. Keywords: Work Discipline, Employee Performance, Performance Improvement Efforts